2013
DOI: 10.1002/prot.24238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel ligand binding site in phosphoserine phosphatase from the hyperthermophilic archaeon Thermococcus onnurineus

Abstract: Phosphoserine phosphatase (PSP) catalyzes the final and irreversible step of L-serine synthesis by hydrolyzing phosphoserine to produce L-serine and inorganic phosphate. Developing a therapeutic drug that interferes with serine production is of great interest to regulate the pathogenicity of some bacteria and control D-serine levels in neurological diseases. We determined the crystal structure of PSP from the hyperthermophilic archaeon Thermococcus onnurineus at 1.8 Å resolution, revealing an NDSB ligand bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…S2 in the supplemental material). The genes in the third subfamily (GDP2 to GDP4) have an additional feature: they carry an N-terminal HAD domain encoding a hydrolase sequence with homology to the enzyme 3-phosphoserine phosphatase (PSP), which catalyzes the final and irreversible step of serine biosynthesis (54). The Arabidopsis member of the subfamily lacks this domain, but it is present in the V. carteri member.…”
Section: Resultsmentioning
confidence: 99%
“…S2 in the supplemental material). The genes in the third subfamily (GDP2 to GDP4) have an additional feature: they carry an N-terminal HAD domain encoding a hydrolase sequence with homology to the enzyme 3-phosphoserine phosphatase (PSP), which catalyzes the final and irreversible step of serine biosynthesis (54). The Arabidopsis member of the subfamily lacks this domain, but it is present in the V. carteri member.…”
Section: Resultsmentioning
confidence: 99%
“…The optimum temperature for bmPSP activity was found to be 37 °C, which was lower than those of PSPs from hyperthermophilic Thermococcus onnurineus (65 °C) and Me. jannaschii (70 °C) (Wang et al ., ; Jung et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…hyperthermophilic Thermococcus onnurineus (65 C) and Me. jannaschii (70 C) (Wang et al, 2002;Jung et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The present observation that NDSB‐195 enhanced the dynamics of Gly53 residue indicates that this compound accelerates the conformational changes between the type II and type I β‐turns adopted by residues Glu51–Arg54. Because the hydrogen bond between the amide proton of Gly53 and the side‐chain carboxylate group of Asp24 is formed in the type II β‐turn but not in the type I β‐turn and because the sulfonate group of NDSB molecules is reported to form a hydrogen bond with a backbone amide proton of phosphoserine phosphatase of Thermococcus onnurineus (4AP9.pdb) , NDSB‐195 is inferred to promote both the formation and the breakage of the hydrogen bond. If the NDSB‐195 promoted only the breakage of the hydrogen bond, the equilibrium between the type II and type I β‐turns would shift toward the type I; then, a large chemical shift change in the upfield direction would have been observed for the amide proton signal of Gly53 .…”
Section: Discussionmentioning
confidence: 99%
“…Non‐detergent sulfobetaines (NDSBs; Figure ) are a new group of small, synthetic protein stabilizers, which have some advantages over osmolytes: they do not increase solution viscosity, unlike polyols; they are zwitterionic at all pH ranges; and they do not increase ionic strength nor perturb pH, unlike amines and amino acids . In addition to the stabilizing effects, NDSBs are known to facilitate the crystallization of proteins and refolding of denatured proteins . We found that, compared with osmolytes, NDSBs exhibit more potent activity to protect human islet amyloid polypeptides from amyloid formation .…”
Section: Introductionmentioning
confidence: 99%